Highly oriented and polyoxometalate-incorporating surface-attached metal–organic frameworks for efficient dye adsorption and water oxidation. Issue 46 (10th November 2020) - Yu, Xiu-Jun; Zhong, Hai; Xian, Yi-Ming; Wang, Ze-Ping; Schneider, Sebastian; Scherr, Julian; Abu-Husein, Tarek; Zhang, Zhuo; Terfort, Andreas
Abstract : We present a facile protocol for the controlled growth of highly oriented and polyoxometalate-incorporating HKUST-1 SURMOFs, which exhibit excellent abilities in dye adsorption and water oxidation. Abstract : We present a facile protocol for the controlled growth of highly oriented and polyoxometalate-incorporating HKUST-1 SURMOFs. Combining the spin-coating technique with alcohol-vapour induced growth, film thickness, crystallite orientation and crystal size can be precisely tuned. The SURMOFs exhibit excellent abilities in selective adsorption of cationic dyes and water oxidation.